2008
DOI: 10.1073/pnas.0803230105
|View full text |Cite
|
Sign up to set email alerts
|

A search for conserved sequences in coding regions reveals that the let-7 microRNA targets Dicer within its coding sequence

Abstract: Recognition sites for microRNAs (miRNAs) have been reported to be located in the 3 untranslated regions of transcripts. In a computational screen for highly conserved motifs within coding regions, we found an excess of sequences conserved at the nucleotide level within coding regions in the human genome, the highest scoring of which are enriched for miRNA target sequences. To validate our results, we experimentally demonstrated that the let-7 miRNA directly targets the miRNA-processing enzyme Dicer within its … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

16
398
2

Year Published

2010
2010
2016
2016

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 534 publications
(420 citation statements)
references
References 34 publications
(40 reference statements)
16
398
2
Order By: Relevance
“…Our present study revealed that miR-484 can repress Fis1 expression through targeting its amino acid coding sequence rather than its 3′-UTR. This is in consistence with the most recent work demonstrating that miRNAs can interact with the coding region of mRNA 45,46 . For example, miR-148 represses DNA methyltransferase 3b gene expression through a region in its coding sequence 47 .…”
Section: Discussionsupporting
confidence: 85%
“…Our present study revealed that miR-484 can repress Fis1 expression through targeting its amino acid coding sequence rather than its 3′-UTR. This is in consistence with the most recent work demonstrating that miRNAs can interact with the coding region of mRNA 45,46 . For example, miR-148 represses DNA methyltransferase 3b gene expression through a region in its coding sequence 47 .…”
Section: Discussionsupporting
confidence: 85%
“…These targets include loci in the protein-coding region of mRNAs (8)(9)(10)(11)(12)(13), 5′ UTRs (14), intronic and intergenic transcripts (15,16), and other non-protein-coding RNAs (ncRNAs) (17,18), as well as embedded B retroelements (13,19), pseudogenes (20), short interspersed elements (SINEs) (21), and circular RNAs (22,23). As technological and research advances reveal a larger and more diverse spectrum of miRNA targets, the related question of how many miRNAs are encoded by an organism's genome becomes one of renewed importance.…”
Section: Significancementioning
confidence: 99%
“…Furthermore, highly conserved seed matches in open reading frames (ORFs) are difficult to identify because of the inherent evolutionary conservation of coding exons. Nonetheless, a growing number of genes have been found to be targeted within the ORF rather than the 3 0 UTR (Forman et al, 2008;Tay et al, 2008). In addition, it was recently pointed out that prediction algorithms utilize sequences from different databases, which contributes to discrepancies in predictions (Ritchie et al, 2009).…”
mentioning
confidence: 99%